Host‐Guest Complexation Between Cyclodextrins and Hybrid Hexavanadates: What are the Driving Forces?. Issue 62 (6th October 2021) - Fa Bamba, Ibrahima; Falaise, Clément; Marrot, Jérôme; Atheba, Patrick; Gbassi, Gildas; Landy, David; Shepard, William; Haouas, Mohamed; Cadot, Emmanuel
Abstract: Host‐guest complexes between native cyclodextrins (α‐, β‐ and γ‐CD) and hybrid Lindqvist‐type polyoxovanadates (POVs) [V6 O13 ((OCH2 )3 C−R)2 ] 2– with R = CH2 CH3, NO2, CH2 OH and NH(BOC) (BOC = N‐tert‐butoxycarbonyl) were studied in aqueous solution. Six crystal structures determined by single‐crystal X‐ray diffraction analysis revealed the nature of the functional R group strongly influences the host–guest conformation and also the crystal packing. In all systems isolated in the solid‐state, the organic groups R are embedded within the cyclodextrin cavities, involving only a few weak supramolecular contacts. The interaction between hybrid POVs and the macrocyclic organic hosts have been deeply studied in solution using ITC, cyclic voltammetry and NMR methods (1D 1 H NMR, and 2D DOSY, and ROESY). This set of complementary techniques provides clear insights about the strength of interactions and the binding host‐guest modes occurring in aqueous solution, highlighting a dramatic influence of the functional group R on the supramolecular properties of the hexavanadate polyoxoanions (association constant K1:1 vary from 0 to 2 000 M −1 ) while isolated functional organic groups exhibit only very weak intrinsic affinity with CDs. Electrochemical and calorimetric investigations suggest that the driving force of the host‐guest association involving larger CDs (β‐ and γ‐CD) is mainly related to the chaotropic effect. In contrast, the hydrophobic effect supported by weak attractive forces appears as the main contributor for the formation of α‐CD‐containing host‐guest complexes. In any cases, the origin of driving forces is clearly related to the ability of the macrocyclic host to desolvate the exposed moieties of the hybrid POVs. Abstract : Hydrophobic or chaotropic effect ? Hybrid Lindqvist‐type polyoxovanadates self‐assemble with cyclodextrins (α‐, β‐, and γ‐) in water to form a wide variety of host‐guest complexes. Such a supramolecular process originates from the ability of the CD host to desolvate the hybrid guests, but the nature of this solvent effect depends on the cyclodextrins, inducing direct consequences on redox properties of the guest.